Bangladesh facing the challenges of globalisation : a review of Bangladesh's development, 2001. - Centre for Policy Dialogue (Bangladesh) (Dhaka : University Press Limited, 2002)
Contributed articles.
"Centre for Policy Dialogue."
"IRBD 2001"--Jacket.
Includes bibliographical references.
BIED
Complimentary copy from BIED
Keywords: Globalization; Bangladesh -- Economic conditions; Bangladesh -- Economic policy